Estudio de factibilidad para la creación de una empresa de yogures artesanales en la ciudad de Bogotá (2019)
The feasibility study for the creation of a company of artisan yogurts in the city of Bogotá is deployed from the analysis of some aspects that affect in one way or another the development of the project; for this reason it is covered from the general diagnosis at Colombia and Bogota level, specifying relevant factors of the manufacturing sector, dairy subsector and others that derive from it; the market segment in which the product will be offered is established, in addition to determining the demand and marketing mix strategies that will drive the market to seek recognition of both the company and the product. At a technical and administrative level that corresponds to the structuring of the company include the description of the product, its respective production process and everything that should be taken into account; additionally, the strategic planning and organizational analysis under which the organization will begin work is determined. On the other hand, and taking into account the environmental commitment that all companies must assume, an environmental study is carried out in order to identify the possible environmental impacts that can be generated and propose the mitigation strategies for them.